Effects of powder dispersion on reactive flash sintering of 8 mol% yttria-stabilized zirconia and MgAl2O4 composites. (December 2020) - Yoon, Bola; Avila, Viviana; Kathiria, Rushi; Jesus, Lílian M.
Abstract: A three-phase system consisting of alumina (Al2 O3 ), magnesia (MgO) and 8 mol% yttria‐stabilized zirconia (8YSZ) was reactive flash sintered to produce MgAl2 O4 -8YSZ composites. We show that a critical volume fraction of the ionic conductor 8YSZ is required to promote the flash phenomenon, indicating a typical percolation behavior. The easy path for conduction could be reached with a smaller critical volume fraction when using agglomerated powders for producing the green bodies. Furthermore, microstructure and X-ray diffraction analyses demonstrate that both sintering and phase transformation largely depend on the mixing level of the precursors. Although the presence of agglomerates resulted in a decrease of the flash onset temperature, poor sintering and incomplete phase transformation were verified. This behavior is attributed to inhomogeneous heat distribution within those samples during the flash state, which could be explained by the electrical current percolation. Graphical abstract: Image, graphical abstract